An empirical Investigation of liquidity and stock returns relationship in Vietnamese stock market - Nguyen, Thi Kim Duyen (H. : ĐHQGHN, 2020)
The study showed the positive relationship between liquidity and stock returns, which contradicts the negative correlation typically found in developed market but is compatible with those researches in emerging market like Vietnam.